Epidemiology of acute febrile illness in Latin America. (August 2018) - Moreira, J.; Bressan, C.S.; Brasil, P.; Siqueira, A.M.
Abstract: Background: The causes of acute febrile illness (AFI) in Latin America are diverse and their complexity increases as the proportion of fever due to malaria decreases, as malaria control measures and new pathogens emerge in the region. In this context, it is important to shed light on the gaps in the epidemiological characteristics and the geographic range for many AFI aetiologies. Objectives: To review studies on community-acquired fever aetiology other than malaria in Latin America, and to highlight knowledge gaps and challenges needing further investigation. Sources: PubMed from 2012 to April 2018. Content: We found 17 eligible studies describing 13 539 patients. The median number of pathogens tested per individual was 3.5 (range 2–17). A causative pathogen could be determined for 6661 (49.2%) individuals. The most frequently reported pathogen during the study periods was dengue virus (DENV) (14 studies), followed by chikungunya virus (nine studies) and Zika virus (seven studies). Among the studies reporting concurrent infections, 296 individuals (2.2%) were found to have co-infections. In-hospital mortality was reported in eight (47%) studies, ranging between 0% and 18%. Implications: DENV fever is the febrile illness most frequently reported, reflecting its importance, while chikungunya and zika viruses present increasing trends since their emergence in the region. Studies with systematic and harmonized approaches for detection of multiple pathogens are needed and would probably reveal a higher burden of neglected pathogens such as Rickettsia spp. and arenaviruses. The lack of point-of-care tests and harmonized approach limits the care provided by health professionals and the efficacy of surveillance for AFI in the region.